Leitura e produção textual: didatização sociocognitiva do gênero discursivo tirinha - Sales, Glaucia Maria de (2015)
This study aims to develop a reading and text production project using the discursive genre ‘comic strip’, applied in a 5th grade class of elementary school, composed by twenty students, in the municipality of Santa Rita - Paraiba, and to present the results of the project. After a diagnosis made with the present group, we confirmed the deficiencies in reading and writing production of the comic strip genre. Furthermore, we noticed that the teaching guidelines in textbooks aimed at the production of written comic strips are still scarce, which also justified the development of a pedagogical intervention project, aiming at overcoming these difficulties. The teaching of Portuguese Language from genres presents an indicator of the main limitations in reading and writing present in the classroom, in addition to serving as a guide to conduct the teacher in his teaching acting and development of teaching material facing these mishaps. Thus, this study was anchored by theoretical assumptions of Bakhtin (2011) and Fiorin (2006) about discursive genres, the research of Marcuschi (2008), the study of Solé’s reading strategies (1998), the research on the teaching of reading and text production from genres by Koch and Elias (2012, 2013), among others, and following the guidelines of the PCN (1998). Following the model of the didactic sequence proposed by Lopes-Rossi (2011), the project was divided into two stages: 1st) reading project, which was divided into four moments; 2nd) written production project, divided into six moments. Regarding the methodological procedures used as the basis for the analysis of our corpora, which are the reading activities and strips produced by the students at the end of the project, we made a comparative analysis between the diagnosis activity and the written productions, after the application of the didactic sequence, paying attention to the discursive and compositional aspects of the gender comic strip. Confirming our hypothesis, the analysis of the results indicates that after the development of the intervention project, there have been significant advances in the reading and written production of the students.